IMPLIKASI PEMILIHAN KEPALA DAERAH SERENTAK SEBAGAI PERWUJUDAN DEMOKRASI PADA MASA PANDEMI COVID 19 DI KABUPATEN PESISIR SELATAN - Aqri Febri Handra (UNES Law Review, 2022)
Simultaneous Pilkada in 2020 should be used as the beginning for quality democracy. The COVID-19 pandemic has caused several changes in the implementation of regional elections, in accordance with KPU Decree Number: 179/PL.02-kpt/01/KPU/III/2020 concerning Postponing the Stages of Elections for Governors and Deputy Governors, Regents and Deputy Regents, and/or Mayor and Deputy Mayor in 2020 in Efforts to Prevent the Spread of Covid-19. These regulations, among others, regulate the postponement of the 2020 Pilkada stages in several parts, such as the inauguration and tenure of the Voting Committee (PPS), verification of the support requirements of individual candidates, the formation of a Voter Data Update Officer (PPDP) and the implementation of matching and research (coklit), as well as updating and preparation of voter lists. Analysis and discussion of the results obtained the following answers: (a) The implications of implementing simultaneous regional head elections as a manifestation of democracy during the Covid 19 pandemic in Pesisir Selatan Regency, namely increasing voter participation in the 2020 Pilkada compared to the 2015 Pilkada. The next implication is the emergence of disputes over the results of the vote in the election. (b) Obstacles in the implementation of simultaneous regional head elections as a manifestation of democracy during the Covid 19 pandemic in Pesisir Selatan Regency, namely the non-neutrality of the State Civil Apparatus in organizing the Pilkada by committing violations at several stages of the election